The influence of spatial variability of solar radiation on the mass balance of glaciers in the Grønfjorden Bay area (the Svalbard archipelago) - A. V. Terekhov; U. V. Prokhorova; V. E. Demidov (Лëд и снег)
In this article, we investigate how the irregular insolation of two low-elevated Svalbard glaciers exerts effect on rates of their surface melting. We compare the spatial distribution of rates of the surface lowering of glaciers Vøringbreen (0.76 km2) and Aldegondabreen (5.5 km2), both are located near Barentsburg settlement in the western part of Nordenskiöld Land (the Spitsbergen Island). As an approximation of the solar radiation flux, we used the potential incoming solar radiation calculated by the ArcticDEM digital elevation model for the period July 15–September 15, which is a typical time of ice ablation in the region under consideration. Motions of both glaciers are extremely slow, which allows assuming that lowering of their surfaces are identical to the rates of surface melting. We have found that both glaciers are distinctly divided into two parts, more and less sunlit. The spatial pattern of insolation of the Vøringbreen glacier is controlled by the shading of the walls surrounding the cirque, while the Aldegondabreen one due to its concave shape has two different areas with a more southern and more northern exposure. The lowering of the surface shows that the more and less illuminated parts differ significantly in ice ablation. The maximum differences in melting caused by the irregular insolation are 2.1 m of ice depth over five years for the Aldegondabreen Glacier (2008–2013 and 2013–2018) and 2.2 m over six years for the Vøringbreen Glacier (2013–2019), that is 40, 30 and 25% of the total values of the surface depression for the corresponding periods. Within every 50-meter altitude interval, correlation coefficients between surface ablation and insolation vary from –0.33 to –0.62 for the Aldegondabreen and from –0.50 to –0.92 for the Vøringbreen glacier. When compared with the vertical gradient of the ice melting, the variability of ablation caused by the irregular insolation correspond to a difference in altitudes of 45–50 m in vertical for the Aldegondabreen and 60 m for Vøringbreen. These values are significant taking into account the small altitudinal range of the glaciers in that part of Spitsbergen.